Parental responsibilities as represented in Malay proverbs - David, Maya Khemlani; Mohd. Noor, Faridah Noor (Journal of Modern Languages, 2013)
Proverbs have been generally defined as self-contained, pithy traditional expressions with didactic content and fixed poetic form. These traditional expressions reflect the traditional beliefs and prejudices of a community (Norrick 1985 28), the world view or the weltanschauung of the community. Proverbs therefore provide an insight about people and its culture. More importantly, from the perspective of this paper, the proverbs of a specific speech community are seen to mirror the attitudes and value systems of the community. The focus of this paper is on a collection of Malay proverbs on child rearing. About sixty proverbs collated from seven (7) sources are examined to determine how the Malays of Malaysia perceive the role of parenting and the duties of children towards their parents and siblings. These were categorised according to the major themes that arose from the data. As proverbs generally consist of abstract comparisons to object/s and or event/s a secondary objective of the paper was to determine and analyze the kinds of imagery used in these proverbs.